2012
DOI: 10.2298/jsc110121182n
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of short chain phenylalkanoic acids within ionic surfactant micelles in aqueous media

Abstract: % SDS KR nema Solubilization and interactions of phenylalkanoic acids induced by cationic surfactant, cetyltrimethylammonium bromide (CTAB) and an anionic surfactant, sodium dodecyl sulfate (SDS) was investigated spectrophotometrically at 25.0°C. The UV spectra of the additives (acids) were measured with and without surfactant above and below critical micelle concentration (cmc) of the surfactant. The presence of alkyl chain in phenylalkanoic acids is responsible for hydrophobic interaction resulting in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…For the NIC/SDS system, the values of K x and K b were estimated to be 9.66 9 10 4 and 233, respectively. The negative values of DG p and DG b (-28.44 and -13.51 kJ mol -1 , respectively) for this system reveal the spontaneity of partitioning, binding, and stability of the system [14,[17][18][19][20][21][26][27][28]. Similarly for the NIC/SS system, the values of K x are K b are 6.6 9 10 4 and 143, respectively, and DG p and DG b are -27.50 and -12.29 kJ mol -1 , respectively.…”
Section: Differential Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…For the NIC/SDS system, the values of K x and K b were estimated to be 9.66 9 10 4 and 233, respectively. The negative values of DG p and DG b (-28.44 and -13.51 kJ mol -1 , respectively) for this system reveal the spontaneity of partitioning, binding, and stability of the system [14,[17][18][19][20][21][26][27][28]. Similarly for the NIC/SS system, the values of K x are K b are 6.6 9 10 4 and 143, respectively, and DG p and DG b are -27.50 and -12.29 kJ mol -1 , respectively.…”
Section: Differential Spectroscopymentioning
confidence: 99%
“…Free energy change, binding constant (K b ), and partition coefficients are helpful for the characterization of thermodynamic phenomena of complex-surfactant interaction and transfer of complex between bulk water and micellar phases, respectively. The structure of complex and surfactant constituting the micelles has a strong effect on the partition coefficient [14,[16][17][18]. In this manuscript, we report the influence of two anionic surfactants (sodium dodecylsulfate and sodium stearate) on micellar solubilization of the hexakis(imidazole)nickel(II) fluoride pentahydrate complex (NIC) to infer how this complex behaves in aqueous solution and how it interacts with anionic surfactants.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, their small-angle neutron scattering results revealed that the rodlike Triton X-100 micelles with the increased micellar aggregation number are formed on progressive solubilization of FA. Generally, the addition of hydrophobic phenolic acids like FA could reduce the critical micelle concentration of surfactants and change the structural and rheological properties of surfactant micelles. , Obviously, the physicochemical properties and bioactivities of FA with surfactant micelles are significantly related with the molecular interactions between FA and surfactants of diverse structures.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the addition of hydrophobic phenolic acids like FA could reduce the critical micelle concentration of surfactants and change the structural and rheological properties of surfactant micelles. 8,9 Obviously, the physicochemical properties and bioactivities of FA with surfactant micelles are significantly related with the molecular interactions between FA and surfactants of diverse structures.…”
Section: ■ Introductionmentioning
confidence: 99%